Пети разред основне школе

Одузимање разломака

Дефиниција, особине, решени задаци.

Задаци

Текст задатака објашњених у видео лекцији:

Пр.1)   Израчунати:

            а) $\frac{4}{5} - \frac{2}{5}$

            б) $\frac{7}{9} - \frac{1}{9}$

            в) $3\frac{2}{3} - 2\frac{1}{3}$

            г) $2\frac{3}{8} - 1\frac{3}{8}$

            д) $3\frac{1}{9} - 1\frac{5}{9}$
            ђ) $3 - 1\frac{3}{7}$
Пр.2)   Израчунај:
           а) $\frac{1}{2} - \frac{1}{3}$
           б) $\frac{3}{5} - \frac{3}{7}$
           в) $\frac{5}{6} - \frac{3}{4}$
           г) $5\frac{7}{{10}} - 1\frac{2}{5}$
           д) $3\frac{1}{6} - \frac{1}{4}$
           ђ) $6\frac{1}{2} - 5\frac{2}{3}$
           е) $\frac{5}{6} - \frac{1}{3} - \frac{1}{4}$

           ж) $5 - \frac{1}{3} - 3\frac{5}{6}$

           з) $5\frac{4}{5}2\frac{5}{6} - 1\frac{9}{{10}}$

 

 Пр.1)       а) $\frac{4}{5} - \frac{2}{5} = \frac{{4 - 2}}{5} = \frac{2}{5}$

            б) $\frac{7}{9} - \frac{1}{9} = \frac{{7 - 1}}{9} = \frac{6}{9} = \frac{2}{3}$

            в) $3\frac{2}{3} - 2\frac{1}{3} = 1\frac{{2 - 1}}{3} = 1\frac{1}{3}$

            г) $2\frac{3}{8} - 1\frac{3}{8} = 1$

            д) $3\frac{1}{9} - 1\frac{5}{9} = 2\frac{{10}}{9} - 1\frac{5}{9} = 1\frac{5}{9}$
            ђ) $3 - 1\frac{3}{7} = 2\frac{7}{7} - 1\frac{3}{7} = 1\frac{4}{7}$
 
Пр.2)  а) $\frac{1}{2} - \frac{1}{3} = \frac{3}{6} - \frac{2}{6} = \frac{1}{6}$
           б) $\frac{3}{5} - \frac{3}{7} = \frac{{21}}{{35}} - \frac{{15}}{{35}} = \frac{6}{{35}}$
           в) $\frac{5}{6} - \frac{3}{4} = \frac{{10}}{{12}} - \frac{9}{{12}} = \frac{1}{{12}}$
           г) $5\frac{7}{{10}} - 1\frac{2}{5} = 5\frac{7}{{10}} - 1\frac{4}{{10}} = 4\frac{3}{{10}}$
           д) $3\frac{1}{6} - \frac{1}{4} = 3\frac{2}{{12}} - \frac{3}{{12}} = 2\frac{{14}}{{12}} - \frac{3}{{12}} = 2\frac{{11}}{{12}}$
           ђ) $6\frac{1}{2} - 5\frac{2}{3} = 6\frac{3}{6} - 5\frac{4}{6} = 5\frac{9}{6} - 5\frac{4}{6} = \frac{5}{6}$
           е) $\frac{5}{6} - \frac{1}{3} - \frac{1}{4} = \frac{{10}}{{12}} - \frac{4}{{12}} - \frac{3}{{12}} = \frac{3}{{12}} = \frac{1}{4}$

           ж) $5 - \frac{1}{3} - 3\frac{5}{6} = 4\frac{6}{6} - \frac{2}{6} - 3\frac{5}{6} = 4\frac{4}{6} - 3\frac{5}{6} = 3\frac{{10}}{6} - 3\frac{5}{6} = \frac{5}{6}$

           з) $5\frac{4}{5} - 2\frac{5}{6} - 1\frac{9}{{10}} = 5\frac{{24}}{{30}} - 2\frac{{25}}{{30}} - 1\frac{{27}}{{30}} = 4\frac{{54}}{{30}} - 2\frac{{25}}{{30}} - 1\frac{{27}}{{30}} = 1\frac{2}{{30}} = 1\frac{1}{{15}}$